Self-nanomicellizing solid dispersion of edaravone: part I – oral bioavailability improvement - Parikh A; Kathawala K; Tan CC; Garg S; Zhou XF (Dove Medical Press, 2018)
Ankit Parikh, Krishna Kathawala, Chun Chuan Tan, Sanjay Garg, Xin-Fu Zhou School of Pharmacy and Medical Sciences, University of South Australia, Adelaide, SA, Australia Background: Edaravone (EDR) is known for its free radical scavenging, antiapoptotic, antinecrotic, and anticytokine effects in neurological and non-neurological diseases. It is currently available clinically as Radicava® and Radicut®, intravenous medications, recently approved for the treatment of amyotrophic lateral sclerosis and cerebral infarction. However, the oral use of EDR is still restricted by its poor oral bioavailability (BA) due to poor aqueous solubility, stability, rapid metabolism, and low permeability. The present study reports the development of novel EDR formulation (NEF) using self-nanomicellizing solid dispersion (SNMSD) strategy with the aim to enable its oral use. Materials and methods: The selection of a suitable carrier for the development of NEF was performed based on the miscibility study. The optimization of EDR-to-carrier ratio was conducted via kinetic solubility study after preparing SNMSDs using solvent evaporation technique. The drug–polymer carrier interaction and self-nanomicellizing properties of NEF were investigated with advanced characterization studies. In vitro permeation, metabolism, and dissolution study was carried out to examine the effect of the presence of a carrier on physicochemical properties of EDR. Additionally, the dose-dependent pharmacokinetic study of NEF was conducted and compared with the EDR suspension. Results: Soluplus® (SOL) as a carrier was selected based on the potential for improving aqueous solubility. The NEF containing EDR and SOL (1:5) resulted in the highest enhancement in aqueous solubility (17.53-fold) due to amorphization, hydrogen bonding interaction, and micellization. Moreover, the NEF demonstrated significant improvement in metabolism, permeability, and dissolution profile of EDR. Furthermore, the oral BA of NEF showed 10.2-, 16.1-, and 14.8-fold enhancement compared to EDR suspension at 46, 138, and 414 µmol/kg doses. Conclusion: The results demonstrated that SNMSD strategy could serve as a promising way to enhance EDR oral BA and NEF could be a potential candidate for the treatment of diseases in which oxidative stress plays a key role in their pathogenesis. Keywords: edaravone, Soluplus®, nanotechnology, oral bioavailability, metabolism, permeability